Antimicrobial activity, genome analysis, and gene cluster encoding the plantaricin production of Lactiplantibacillus plantarum ZBK1-5 - Natladda Choovet; Thanadol Jirakanjanasit; Punyavee Subphon; Supranee Thepsombat; Engkarat Kingkaew; Naoto Tanaka; Yuh Shiwa; Somboon Tanasupawat; Sukanya Phuengjayaem (ScienceAsia, 2024)
This study aimed to explore bacteriocin-producing lactic acid bacteria (LAB), identify the genes influencing bacteriocin synthesis, and assess their probiotic potential via safety evaluations both in vitro and in silico.The strain ZBK1-5, isolated from pickled ginger, was identified as Lactiplantibacillus plantarum.The bacteriocin ZBK1-5 exhibited the highest antimicrobial activity with 6,400 AU/ml at 18 h, predominantly effective against Gram-positive bacteria and stable within pH 2-9.Significantly, the genome analysis confirmed the existence of bacteriocin synthesis genes, specifically plantaricin KJ, EF, A, and N. Simultaneously, the safety evaluations showed its low risk of antibiotic resistance gene transfer, thereby emphasizing the safety profile of the strain ZBK1-5.The genetic components associated with the ability of L. plantarum ZBK1-5 to survive and adapt in gastrointestinal conditions provide additional evidence (16 genes related to acid stress and 9 genes associated with bile resistance), supporting its potential as a probiotic candidate.These findings were validated through in vitro digestion conditions, where the viability of the cells was observed to be 68.26,66.62, and 60.91% during transit through the oral, gastrointestinal, and small intestinal phases, respectively.Additionally, the strain ZBK1-5 showed a 90.39% adhesion rate in the Caco-2 cell line.The unique characteristics of plantaricin produced by L. plantarum ZBK1-5 exhibit potent antibacterial activity, rapid time to production compared to other known plantaricins, and strain safety for application and upscaling.This research study offers significant scientific insights into L. plantarum ZBK1-5, a plantaricin producer, emphasizing its promising potential for future applications.
Keywords: Medicinal Plants and Neuroprotection; Microbial Metabolism and Applications; Biochemical and Structural Characterization